A Head-to-head Comparison between SurgiMend and Epiflex in 127 Breast Reconstructions. Issue 6 (June 2015) - Eichler, Christian; Vogt, Nadine; Brunnert, Klaus; Sauerwald, Axel; Puppe, Julian; Warm, Mathias
<x xml:space="preserve">Abstract</x> Background: The use of acellular dermal matrices (ADM) has become a widely used option in breast reconstruction. A great deal of literature is available, totaling over 2400 ADM reconstructions. Nonetheless, head-to-head comparisons between SurgiMend and Epiflex are not yet reported. In fact, this is the first clinical data report on the use of Epiflex. This work will, therefore, compare postoperative complication rates and costs for these ADMs. Methods: This analysis is a retrospective review of a single surgeon's 6-year experience with both SurgiMend—an acellular bovine dermal collagen matrix for soft-tissue reconstruction and Epiflex—a decellularized human skin tissue from 2008 to 2013. Results: One hundred patients had a total of 127 implant-based reconstructions using SurgiMend (64 cases; 50.4%) or Epiflex (63 cases; 49.6%). Gross complication rates were 11.1% for SurgiMend and 40.6% for Epiflex including hematoma, postoperative skin irritation, infection, necrosis, and revision surgery. The most common complication was postoperative red breast syndrome. Severe complications requiring revision surgery were significantly increased in patients treated with Epiflex (12.5%) compared with SurgiMend (4.8%). Conclusions: This retrospective analysis favors the use of SurgiMend over Epiflex because of significantly lower gross complication rates. Severe complication rates are comparable with those reported in literature for both products. Although results promote the use of SurgiMend, the single surgeon retrospective nature of this work limits its clinical impact.